What Motivates Government Doctors in India to Perform Better in their Job?. (March 2014) - Bhatia, Shalini; Purohit, Bhaskar
Objectives: Addressing the issue of poor motivation of Medical Officers (MOs) to join and continue service in rural India is a major challenge faced by the health system. The present study aimed at assessing the driving factors of motivation for MOs working with rural government health centres in India. The study also aimed at finding out the differences in the preferred factors of motivation based on various job-related aspects of the respondents. Methods: The study participants included MOs from Gujarat, India. The study asked the participants to rank 20 factors of motivation (10 intrinsic and 10 extrinsic motivation factors) important for them to continue in their current job. The factors for the study were selected using Herzberg's two factor theory of motivation and the data was collected with the help of an instrument that has an established reliability and validity. Distribution of ranks of different motivating factors was studied using average ranks assigned by respondents based on different job-related aspects. Average scores were also calculated to see whether the respondents are motivated more by extrinsic factors or by intrinsic factors. Results: The results indicate that 'job security' was the most preferred factor of motivation followed by 'adequate salary' while, the least preferred factor for motivation was 'local political interference'. Adequate salary and job security also emerged as the two most important motivation factors for all the three groups of respondents based on number of years of work experience. For Ad hoc MOs, 'adequate salary' and 'interesting work' were the most important motivation factors while for bonded category of MOs, 'adequate salary' and 'opportunities for promotion' were the two most important factors for motivation. Conclusion: The current study concludes that MOs motivation to continue with the current job is driven both by extrinsic and intrinsic factors. Hence, the health departments and systems need to pay close attention to devising strategies that address both the extrinsic as well as intrinsic factors. However, according to study findings, more attention needs to be paid to providing Job security and better salaries and monetary benefits to MOs. The study results may be useful to health departments and systems to design management strategies that are based on motivational needs of MOs to improve their attraction and retention.